2014
DOI: 10.1186/1756-0500-7-759
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin and methicillin-resistant Staphylococcus aureus isolated from a catheter-related bloodstream infection: a case report

Abstract: BackgroundDaptomycin is an alternative option for the treatment of catheter-related bloodstream-infections caused by methicillin-resistant Staphylococcus aureus. This study reports a case of a daptomycin and methicillin-resistant Staphylococcus aureus isolate recovered from the blood of a Brazilian patient undergoing hemodialysis.Case presentationA 64-year-old white male patient suffering from diabetes mellitus, systolic hypertension, heart disease with a coronary stent, obesity and chronic renal failure and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In the present study, the results showed that although not all patients were located at the same ward, or even hospitalized at the same time, a possible dissemination of the USA100/ST5 lineage may have occurred in the hospital, probably carried by the hospital professionals. As in our study [ 13 ], we found that four of the six patients with BSI caused by VISA isolates had undergone dialysis treatment before isolation of a VISA strain. Vancomycin is a key antibiotic for the treatment of gram-positive infections and this may select for the VISA phenotype [ 7 ], [ 33 ], [ 34 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In the present study, the results showed that although not all patients were located at the same ward, or even hospitalized at the same time, a possible dissemination of the USA100/ST5 lineage may have occurred in the hospital, probably carried by the hospital professionals. As in our study [ 13 ], we found that four of the six patients with BSI caused by VISA isolates had undergone dialysis treatment before isolation of a VISA strain. Vancomycin is a key antibiotic for the treatment of gram-positive infections and this may select for the VISA phenotype [ 7 ], [ 33 ], [ 34 ].…”
Section: Discussionsupporting
confidence: 61%
“…Despite a previous report of vancomycin resistant S . aureus (VRSA) isolated from a bloodstream infection in São Paulo in 2013 [ 10 ], hVISA [ 11 ] and VISA [ 12 ], [ 13 ] isolates appear to be uncommon in Brazil. We previously reported that 124 S .…”
Section: Introductionmentioning
confidence: 99%
“…This lineage has also been observed in blood samples in Brazil, highlighting that one of these reports describes two isolates of S. aureus resistant to daptomycin. 27 In Brazil, to the best of our knowledge, there are few reports of USA600/ST45-MRSA-IV isolates, which were collected from skin infection case and from catheter. 23 , 28 …”
mentioning
confidence: 99%
“…The emergence of daptomycin-resistant S. aureus is relatively uncommon. However, increasing records of daptomycin-resistant S. aureus have been reported [31][32][33].…”
Section: Daptomycinmentioning
confidence: 99%